Perennial halophyte Salicornia neei Lag.: Cell wall composition and functional properties of its biopolymers - Villarreal, Matias Ricardo (2021)
Salicornia neei halophyte extends in Argentina seashores. To envisage potential applications, cell wall sequential extraction performed on dry plant yielded 1.1, 2.4, 0.3 and 0.9% of pectin fractions respectively extracted by room temperature water, 90 °C-water, CDTA and Na2CO3. They contained 21–33% uronic acids (UA) with low degree of methylation and 0.5–1.2 M ratios of neutral sugars to UA. High arabinose level suggests that long arabinan side-chains maintain cell wall flexibility in water deficit. Fractions also contained 10–36% of proteins. The KOH-soluble fractions (4.3%) were mainly arabinoxylans. At 2.0% w/v, pectin fractions developed “weak gel”-type networks with Ca2+, while arabinoxylans generated “dilute solutions”. Cellulose (28%) and lignin (45.1%) were the main biopolymers in the final residue, which showed low water swelling capacity (3.6 mL/g) due to lignin, increasing when arabinoxylans were also present. Phenolics (9.8%) were mainly water-extractable. Salicornia is a source of biopolymers and antioxidants potentially useful for food applications.